2008
DOI: 10.1007/s00348-008-0569-2
|View full text |Cite
|
Sign up to set email alerts
|

Correction of wandering smoothing effects on static measurements of a wing-tip vortex

Abstract: Wandering is a typical feature of wing-tip vortices and it consists in random fluctuations of the vortex core. Consequently, vortices measured by static measuring techniques appear to be more diffuse than in reality, so that a correction method is needed. In the present paper statistical simulations of the wandering of a Lamb-Oseen vortex are first performed by representing the vortex core locations through bi-variate normal probability density functions. It is found that wandering amplitudes smaller than 60% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 17 publications
2
25
1
Order By: Relevance
“…Consequently, the measured velocity, U p , on an infinitesimal ellipse (x p ; y p ), may be seen as the weighted average of the real velocity, U, associated with the vortex axis displacement, (x v ; y v ) which is modeled by a bivariate probability density function, D w , as proposed by Devenport et al (1996) and confirmed by Heyes and Hubbard (2003) and Iungo et al (2009):…”
Section: Velocity Profile Reconstructionmentioning
confidence: 96%
See 1 more Smart Citation
“…Consequently, the measured velocity, U p , on an infinitesimal ellipse (x p ; y p ), may be seen as the weighted average of the real velocity, U, associated with the vortex axis displacement, (x v ; y v ) which is modeled by a bivariate probability density function, D w , as proposed by Devenport et al (1996) and confirmed by Heyes and Hubbard (2003) and Iungo et al (2009):…”
Section: Velocity Profile Reconstructionmentioning
confidence: 96%
“…In order to deconvolve the underlying velocity field U from our measurements U m according to Eq. 9, two deconvolution methods proposed by Iungo et al (2009) and Devenport et al (1996) may be found in the literature. Iungo's method, which is inspired from blind deconvolution techniques used in astrophysics and medical imaging, requires well-resolved 2D flow fields at each z-location.…”
Section: Velocity Profile Reconstructionmentioning
confidence: 99%
“…Vortex wandering in the near field is caused by external perturbation including background turbulence (Heyes et al 2003;Iungo et al 2009). With increasing wake age, the vortex susceptibility to outer excitation increases.…”
Section: Vortex Wanderingmentioning
confidence: 99%
“…However, single-point scans of vortex flows (such as the hot-wire and multi-hole pressure probe data of Beninati & Marshall (2005), Birch et al (2004), Birch & Lee (2005), Chow et al (1997) and Dacles-Mariani et al (1995), to list but a few) will tend to underpredict vortex strength owing to the smoothing effect of vortex 'meandering', or the random, low-frequency modulation in the trajectory of the vortex centre. While a number of schemes have been proposed to correct single-point scans of vortex wakes for the effect of meandering (such as those of Devenport et al (1996), Bailey & Tavoularis (2008) and Iungo et al (2009)), it has also been shown that, with meandering amplitudes which are large but within the range of those observed experimentally, the reconstruction of the vortex velocity field from point measurements becomes impossible (Birch 2012).…”
Section: Introductionmentioning
confidence: 99%